2017
DOI: 10.1177/1937586717702597
|View full text |Cite
|
Sign up to set email alerts
|

Private Rooms in Low Acuity Settings: A Systematic Review of the Literature

Abstract: Based on CEBM and GRADE assessments, there is a lack of high-quality data supporting the use of low-acuity SBRs throughout the entire hospital. Furthermore, it is recommended that more research be conducted on the effect of SBRs, so higher quality evidence is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 54 publications
2
60
1
Order By: Relevance
“…Similar to previous studies, environmental barriers consisted of poor physical structure and lack of resources, such as poor placement or absence of sinks and handwashing stations [18,36,38,39]. While singlepatient rooms may facilitate patient management [40], our findings and other studies indicate that on their own they are unable to reduce HAI transmission [41][42][43].…”
Section: Discussionsupporting
confidence: 79%
“…Similar to previous studies, environmental barriers consisted of poor physical structure and lack of resources, such as poor placement or absence of sinks and handwashing stations [18,36,38,39]. While singlepatient rooms may facilitate patient management [40], our findings and other studies indicate that on their own they are unable to reduce HAI transmission [41][42][43].…”
Section: Discussionsupporting
confidence: 79%
“…58,59 Regarding patient age (r = −0.277, p = 0.01), this finding was in accordance with previous studies, 56,59 which showed that the satisfaction level decreased with the increase in patients’ age. Although findings of studies conducted in some western countries explored the link between longer hospital stays and decrease in patients’ satisfaction level, 6062 in this study, the results did not find any relationship between patients’ overall level of satisfaction with the duration of the stay at wards (Table 10). This may be due to the family support factor that decreased the effect of a long stay at a hospital on patients’ overall level of satisfaction, especially in Kurdish society, strengthened by the spirit of healing one another, strong family relations and solid familial fabric, social interaction and higher continuum of collective values compared to individualism.…”
Section: Findings and Discussioncontrasting
confidence: 67%
“…Whilst Ulrich et al (2010) highlight the relationships of how healthcare built environments can impact patients and their families, staff and organizational outcomes. In addition, a number of systematic reviews have been conducted around a particular space, care setting or a particular patient category, for example Bartlett (2013) reviewed research evidence related to design features that can be used to create an optimal inpatient psychiatric patient, whilst Taylor et al (2018) and Voigt et al (2018) have reviewed evidence related to the benefits of private-patient rooms, and Benitez, et al (2019) conducted a systematic review on layout planning in Healthcare Facilities.…”
Section: Enhancing Ebd In Practicementioning
confidence: 99%